Transforming agriculture to improve food and nutrition security in Nigeria - Ecker, Olivier; Kennedy, Adam (Michigan State University, 2019)
The current agricultural strategy of the Federal Government of Nigeria—the Agricultural Promotion Policy 2016-2020—carries forward the revitalization of the agricultural sector as outlined in the preceding strategy—the Agricultural Transformation Agenda 2011-2016. The Agricultural Promotion Policy aims to increase agricultural production to meet the food needs of the country’s rapidly growing population and transform agriculture from subsistence to commercial and export-oriented production. The complementary Agricultural Sector Food Security and Nutrition Strategy 2016-2025 declares improved food security and nutrition as main goals of the intended agricultural transformation and identifies priority areas that should guide the activities of the Federal Ministry of Agriculture and Rural Development (FMARD) and aligned stakeholders to achieve these objectives. Both strategy documents emphasize the importance of policy-relevant and rigorous agricultural and nutrition research to inform policy priority setting and support decision-making processes. This policy note summarizes findings from a recent study by International Food Policy Research Institute (IFPRI) researchers that seeks to inform Nigerian policymakers and donors about the effects of agricultural transformation on food and nutrition security of farm households in Nigeria (Ecker et al 2018).